Celiac Disease, Gluten-Free Diet, and Eating Disorders: From Bench to Bedside - Yaohui Wei; Yating Wang; Yonggui Yuan; Jue Chen (Foods)
Celiac disease (CD) and eating disorders (EDs) are complex chronic conditions in adolescents, sharing symptoms such as weight change, malnutrition, and gastrointestinal symptoms. CD, an autoimmune disorder triggered by gluten ingestion, is managed through a strict gluten-free diet that can unintentionally foster disordered eating behaviors due to dietary restrictions. Conversely, EDs may mask and complicate CD symptoms, leading to diagnostic delays and treatment challenges. Evidence reveals an increased risk of EDs in CD individuals and vice versa, indicating a potential bidirectional relationship. This review explores the mechanisms and clinical implications of this interplay and proposes integrated screening and care strategies to improve the quality of life for individuals with both conditions.